PENGUKURAN BEBAN KERJA PEKERJA DI UD. BINTANG JAYA MANDIRI MENGUNAKAN CVL DAN NASA-TLX - Puyuhiyo, Zulqarnain; Wolok, Eduart; Lahay, Idham Halid (Universitas Bina Taruna Gorontalo, 2024)
Abstract: Measuring Workload of Workers at UD. Bintang Jaya Mandiri uses CVL and NASA-TLX The amount of physical and mental load depends on the level of difficulty of each activity, causing different workloads. The method for measuring physical workload uses the %CVL (Cardiovascular Load) method, while the method for measuring mental load uses the NASA-TLX (National Aeronautics and Space Administration Task Load Index) method. Calculation results from workers at UD. Bintang Kaya Mandiri used the %CVL method in shift I. The values ​​obtained were classified as